ANALISIS PERLAKUAN AKUNTANSI ATAS PEMBIAYAAN RAHN (GADAI EMAS SYARIAH): STUDI KASUS PEGADAIAN SYARIAH DI CABANG BANDA ACEH - Eka Zahara Fonna; Maulana Kamal (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2022)
The great interest of the Aceh community in using sharia pawn financing for gold pawn products raises the need for supervision of the accounting treatment implementation of sharia pawn financing in the Islamic financial industry. This study aims to determine the accounting treatment related to the recognition measurement, presentation, and disclosure of Rahn transactions (Islamic gold pawns) that are practiced at the Banda Aceh Sharia Pawnshop. The research method used in this study is descriptive qualitative, with primary and secondary data sources using interviews, observation, and documentation techniques. The author collects data by interviewing cashiers and appraisers at the Banda Aceh branch of the Sharia Pawnshop. The analytical method used is the descriptive analysis method which includes data reduction, display, conclusion drawing, and verification. The results of this study found that the application of accounting treatment in terms of recognition, presentation measurement, and disclosure at the Banda Aceh branch of Islamic Pawnshops is following Indonesian Financial Accounting Standards (PSAK) 107 on ijarah accounting and the Fatwa of the Indonesian National Sharia Council. The results of this study are expected to be an additional reference and study material to develop knowledge in the scope of sharia accounting, especially regarding ijarah accounting.